Creativity and the doctor of philosophy: the case for creativity education within doctoral programs - Daniel, Ryan (Creativity Studies, 2024)
Doctoral education is an increasingly prevalent part of the worldwide higher education landscape. Although there are variations in how programs are constructed and delivered, there is general agreement that evidence of creativity is expected in the final thesis. Despite the significant attention the supervisory process has received in the literature, students’ views on creativity as it applies to their candidature have not been extensively explored. This article reports on interviews with a sample of 12 current doctoral students in the areas of the arts, social sciences, and education from the theoretical perspective of the systems model of creativity. Interview participants were invited to reflect on the concept of creativity, and the factors which support or constrain their potential to be creative. The findings reveal that on reflection, students are able to identify the creative elements of their work, however the findings also indicate that creativity education should be given greater focus in doctoral programs, in order to embed this important concept and process to support students’ learning journey.